Physical Inactivity Among Adults Aged 50 Years and Older — United States, 2014 - Watson, Kathleen B.; Carlson, Susan A.; Gunn, Janelle P.; Galuska, Deborah A.; O’Connor, Ann; Greenlund, Kurt J.; Fulton, Janet E. (MMWR. Morbidity and mortality weekly report, 2016)
Physical activity can help delay, prevent, or manage many of the chronic diseases for which adults aged ≥50 years are at risk (1-3). These diseases can impact the length and quality of life, as well as the long-term ability to live independently.* All adults aged ≥50 years, with or without chronic disease, gain health benefits by avoiding inactivity (2,3). To examine the prevalence of inactivity by selected demographic characteristics and chronic disease status in mid-life and older adults, CDC analyzed data on adults aged ≥50 years from the 2014 Behavioral Risk Factor Surveillance System (BRFSS). Overall, 27.5% of adults aged ≥50 years reported no physical activity outside of work during the past month. Inactivity prevalence significantly increased with increasing age and was 25.4% among adults aged 50-64 years, 26.9% among those aged 65-74 years, and 35.3% among those aged ≥75 years. Inactivity prevalence was significantly higher among women than men, among Hispanics and non-Hispanic blacks than among non-Hispanic whites, and among adults who reported ever having one or more of seven selected chronic diseases than among those not reporting one. Inactivity prevalence significantly increased with decreasing levels of education and increasing body mass index. To help adults with and without chronic disease start or maintain an active lifestyle, communities can implement evidence-based strategies, such as creating or enhancing access to places for physical activity, designing communities and streets to encourage physical activity, and offering programs that address specific barriers to physical activity.